Ring closing metathesis of unprotected peptides. Issue 70 (17th August 2017) - Gleeson, Ellen C.; Jackson, W. Roy; Robinson, Andrea J.
Abstract : Brønsted acid masking of unprotected peptide sequences facilitates high yielding Ru-alkylidene catalysed RCM to cyclic dicarba peptidomimetics in solution. Abstract : An efficient and expedient route to the synthesis of dicarba peptides from protecting group-free sequences is reported using Ru-alkylidene catalysed olefin metathesis. A range of cyclic peptides was prepared from linear peptides containing two Z -crotyl glycine residues. Free amine groups were masked as salts with Brønsted acids preventing in situ catalyst decomposition. Excellent RCM conversion was obtained in both DMF and methanol.